2005
DOI: 10.1111/j.1365-3059.2005.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for studying population structure, including sensitivity to the fungicide silthiofam, of the cereal take‐all fungus, Gaeumannomyces graminis var. tritici

Abstract: Field isolates ( n = 144) of the wheat take-all fungus Gaeumannomyces graminis var. tritici ( Ggt ) were tested for sensitivity to silthiofam, a take-all-specific fungicide used as a seed treatment, and identified as A-or B-type by PCR-RFLP analysis of nuclear rDNA. A possible association was identified between polymorphisms in ITS2 of the nuclear rDNA and sensitivity to silthiofam. A Ggt -specific PCR assay was developed which simultaneously identified isolates of Ggt as A-or B-type, based on the polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 31 publications
(59 reference statements)
2
34
0
Order By: Relevance
“…Recent studies have characterized these genetic groups with regard to biological features such as sensitivity to fungicides and aggressiveness to the host. Both genetic groups, which were characterized from a PCR‐RFLP analysis of nuclear rDNA of Ggt isolated from a wheat crop monoculture, differ in their sensitivity to a seed‐treatment fungicide, silthiofam (Freeman et al ., 2005). Analyses from both RAPD (random amplified polymorphic DNA) and AFLP (amplified fragment length polymorphism) fingerprinting analyses on the same natural populations of Ggt occurring in a wheat monoculture also indicated a distribution into two main genotypes, called G1 and G2 (Lebreton et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have characterized these genetic groups with regard to biological features such as sensitivity to fungicides and aggressiveness to the host. Both genetic groups, which were characterized from a PCR‐RFLP analysis of nuclear rDNA of Ggt isolated from a wheat crop monoculture, differ in their sensitivity to a seed‐treatment fungicide, silthiofam (Freeman et al ., 2005). Analyses from both RAPD (random amplified polymorphic DNA) and AFLP (amplified fragment length polymorphism) fingerprinting analyses on the same natural populations of Ggt occurring in a wheat monoculture also indicated a distribution into two main genotypes, called G1 and G2 (Lebreton et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Primers Ggt fwd (5'-AAG AAC ATC GGC GGT CTC GCC), Ggt Arev (5'-TAG CGG CTG GAG CCC GCC G) and Ggt Brev2 (5'-CTA CCT GAT CCG AGG TCA ACC TAA GG) were designed by Freeman et al [8], using 1x reaction Taq buffer, 1.5 mM MgCl 2 , 0.4 mM dNTPs and DNA 50 ng. Cycling conditions were 35 cycles of 94°C for 30 s, annealing 72°C for 1 min and extension 72°C for 1min, followed by a final extension of 72°C for 10 min.…”
Section: Ggt-specific Identificationmentioning
confidence: 99%
“…In addition, isolates of Ggt were classified as rye-adapted (R) or non-rye-adapted (N) forming distinct groups in dendrograms [7]. On the basis of rDNA analysis using PCR-RFLP method, 144 isolates of Ggt divided into two major groups A and B [8]. Families of short intergenic repeated sequences have been determined in enteric bacteria, primarily Escherichia coli and Salmonella typhimurium.…”
Section: Introductionmentioning
confidence: 99%
“…Primary infections arise from mycelium surviving on infected root and crown debris from previous crops (Hornby, ), while secondary (root‐to‐root) infection also occurs by mycelium growth, either along the roots or through soil, over short distances, typically a few millimetres (Gilligan et al , ). Genotypic studies from different parts of the world and using different molecular tools have consistently shown that populations were structured into two genotypic groups (T1/T2, based on RFLP on mitochondrial ribosomal DNA (Bateman et al , ), G1/G2 based on RAPD and AFLP on nuclear DNA (Lebreton et al , ), N/R based on nuclear rDNA (Bryan et al , ), A/B based on RFLP on nuclear rDNA (Freeman et al , ) and A1/A2 based on RAPD profiles (Augustin et al , )), and these groups are consistent across studies (Daval et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several candidate traits have been proposed, e.g. aggressiveness (Lebreton et al , ), survival between seasons (Van den Berg et al , ), spatial spread (Willocquet et al , ), resistance to fungicides (Freeman et al , ) or sensitivity to antagonistic microflora (Lebreton et al , ). Another mechanism could be the ability to initiate primary infections (i.e.…”
Section: Introductionmentioning
confidence: 99%